Diszkontálási modellek és a hiperbolikus diszkontálás eredményeinek egy lehetséges alkalmazási területe: a nyugdíjelőtakarékosság - Nagy, Sándor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
Nowadays the retirement planning (savings) has become an important issue as the sustainability of pension systems due to negative demographic trends has to face significant risks and threats. The lack of saving induces not only economic but also psychological deliberations and triggering motivations. In this paper I demonstrate such theoretical aspects of behavioral economics, which try to explore and measure the actors' self-control problems.